Towards sustainable business models with a novel life cycle assessment method. (17th February 2022) - Goffetti, Giulia; Böckin, Daniel; Baumann, Henrikke; Tillman, Anne‐Marie; Zobel, Thomas
Abstract: Business model (BM) innovation for sustainability is hampered by a lack of tools for environmental assessment and guidance at the BM level. Conventional life cycle assessment (LCA) neglects the economic and socio‐technical mechanisms within a BM, and tools based on the BM canvas (BMC) cannot provide recommendations substantiated by environmental data. Here, a new method, BM‐LCA, is applied to a case comparing the selling and renting of jackets, using profit as basis of comparison. Results identify how business parameters influence environmental performance, permitting analysis for decoupling within a business practice. This is made possible by the unique way the method links physical life cycle and the monetary flows of a BM. Usefulness of BM‐LCA is discussed relative to BM innovation, business strategy and similar tools. BM‐LCA provides insights into a broad range of BM elements and emerges as useful for business strategy. By measuring BM environmental performance, it helps determine what BM to compete with and support critical analysis of business against greenwashing. BM‐LCA also enables identification of BM elements in greatest need of environmental innovation. BM‐LCA appears as a promising tool for guiding business companies towards sustainability, filling a space between LCA and BMC. The method offers a practical way for business and LCA experts to merge their respective knowledge.